Conhecimento das precauções padrão, prática do reencape de agulhas e condutas frente a acidente com material biológico entre equipes de saúde bucal do Serviço Público Municipal de Araçatuba - SP - Araújo, Thaynara Barbosa de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The oral health teams are vulnerable to que occurrence of biological accidents due to the everyday handling of blood contaminated sharpened materials. Before that finding, efforts have been launched to incentivate the adhesion of preventive measures, called Standard Precautions (SP). This study aimed at verify the knowledge and adhesion to the Standard Precautions, specially the not recapping needles practice; the actions to be taken before accidents and related aspects to infecction prevention, by the oral health teams (dentist and auxilliary staff) of the public service in the Araçatuba city. Also, observe the presence of a sharp disposal container, the filling conditions (over the recommended level or not), the location (close or afar) and the discarded materials in the group E container, in every dental care unity in the city. Was applied a semi-structured questionnaire, with open and closed questions directed to the theme and an specific form to colect the data related to the disposal container. From 79 surveyed individuals, 60 answered to the questionnaire, where 33 (55%) were dentists. 18 (31.6%) of the surveyed affirmed that there was not a protocol to be followed in their work unity and 16 (26,6%) did not had orientation about how to proceed in case of a biological material accident 34 (56.6%) professionals did not know the SP and 49 (81.6%) affirmed not have received any training in their work unity. 27 (44.9%) already suffered some kind of accident involving contaminated sharpened material or blood, being that 10 (16.7%) did not asked to the pacient for sorologic tests e 9 (14.9%) did not reached for medical care after the accident. 43 (71.6%) affirmed to recap needles, using both hands 20 (33.1%), with the justification to not take the risk of an accident during the transportation to the disposal container (40%). 44 (73.3%) ignored... (Complete abstract electronic acess below)

As equipes de saúde bucal estão vulneráveis a ocorrência de acidentes biológicos pelo manuseio diário de materiais perfurocortantes contaminados com sangue e outros fluidos corporais de pacientes. Diante dessa constatação, esforços têm sido lançados para incentivar a adesão a medidas preventivas, denominadas Precauções Padrão (PP). O presente estudo objetivou verificar o conhecimento e adesão às precauções padrão, em especial a prática de não reencapar agulhas; as ações a serem tomadas diante acidentes e aspectos relativos à prevenção de infecções, pelas equipes de saúde bucal (cirurgiõesdentistas e auxiliares em saúde bucal) da rede pública de Araçatuba-SP. Além disso, observar a presença do recipiente de descarte de perfurocortantes, as condições de preenchimento (acima do nível recomendado ou não), sua localização (próxima ou longe do profissional) e os materiais descartados nos recipientes do grupo E, em todas as unidades de atendimento odontológico do município. Aplicou-se um questionário semiestruturado, com perguntas abertas e fechadas direcionadas ao tema e uma ficha especifica para coleta dos dados relativos aos recipientes de descarte. Dos 79 pesquisados, 60 responderam ao questionário, onde 33 (55%) eram cirurgiões-dentistas. 18 (31,6%) afirmaram que não existia um protocolo a ser seguido na unidade em que trabalhavam e 16 (26,6%) que não obtiveram orientação sobre como proceder em caso de acidente com material biológico. 34 (56,6%) profissionais não sabiam o que eram as PP e ainda 49 (81,6%) afirmaram não terem tido nenhum tipo de treinamento na unidade em que estavam trabalhando. 27 (44,9%) já sofreram algum tipo de acidente com material perfurocortante, contaminado ou sangue; sendo que 10 (16,7%) não solicitaram ao paciente fonte a realização de exames sorológicos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Pessoal de saúde; Precauções universais; Contenção de riscos biológicos; Ferimentos penetrantes; Health Personnel